Expectations as reference points: Field evidence from experienced subjects in a competitive, high-stakes environment - Björn Bartling; Leif Brandes; Daniel Schunk (Center for Economic Studies and ifo Institute (CESifo), 2012)
We show that professional soccer players exhibit reference-dependent behavior during matches. Controlling for the state of the match and for unobserved heterogeneity, we show on a minute-by-minute basis that a player breaches the rules of the game, measured by the referee's assignment of cards, with a significantly higher probability if his team is behind the expected match outcome, measured by pre-play betting odds of large professional bookmakers. We derive these results in two independent data sets, one from ten seasons of the German Bundesliga, the other from eight seasons the English Premier League, each with more than half a million minutes of play.
Keywords: D03; D81; D84; L83; 330; reference points; expectations; experience; high stakes; competition; Sportler; Fußballsport; Prospect Theory; Wettbewerb; Professioneller Sport; Schätzung; Deutschland; Großbritannien